Signature of the anthropogenic impacts on the epipelagic microbiome of the North-Western Adriatic Sea (Mediterranean Sea) - Trapella, Giulia; Scicchitano, Daniel; Foresto, Lucia; Dell’Acqua, Andrea Nicoló; Radaelli, Elena; Turroni, Silvia; Rampelli, Simone; Corinaldesi, Cinzia; Palladino, Giorgia; Candela, Marco (Frontiers in Marine Science, 2024)
In our manuscript we explore the impact of different anthropogenic stressors, namely mussel farming, methane extraction platforms and summer mass tourism, on the epipelagic microbiomes of the North-Western Adriatic Sea. By 16S rRNA gene sequencing, we provided the epipelagic microbiome layout from selected sites corresponding to each of the considered impacts. As unimpacted reference, 16S rRNA sequencing data from Scicchitano et al. (2022) have been used. According to our findings, each one of the anthropogenic stressors resulted in a peculiar increase of specific epipelagic microbial components, including copiotrophic R-strategists and host-restricted bacteria, as well as and some pathobiome components, the latter being detected exclusively in impacted sites. Particularly, potentially harmful pathogenic species such as Legionella impletisoli and Staphylococcus epidermidis, has being detected in proximity of the mussel farms and Escherichia coli and Campylobacter ureolyticus, were present close to the methane extraction platform and at the summer mass tourism site, respectively. Particulary, C. ureolyticus is an emerging human gastrointestinal pathogen, capable to destruct intestinal microvilli. Besides providing evidence supporting the existence of recognizable and impact-driven fingerprint on the epipelagic marine microbiome peculiar for the different anthropogenic stressors, our findings also rise the concern of the ecological relevance of the observed changes, not only in terms of possible loss of ecosystem services, but also for the potential release of pathogenic microorganisms in the environment.